Circulating EDIL3 as a Novel Biochemical Indicator of Coronary Microvascular Dysfunction in Patients with ST-Segment Elevation Myocardial Infarction: Circulating EDIL3 and Microvascular Dysfunction in STEMI - Zhang, Zhiyuan; Hu, Chunfang; Wang, Jian; Wang, Ruzhu; Ruan, Zhongbao; Zhu, Li (Journal of Medical Biochemistry, 2026)
Background: Developmental endothelial locus-1 (EDIL3) is an extracellular matrix-associated glycoprotein involved in endothelial activation, inflammatory regulation, and vascular remodeling. However, the clinical significance of circulating EDIL3 in ST-segment elevation myocardial infarction (STEMI), particularly in relation to coronary microvascular dysfunction, remains unclear. This study aimed to investigate the dynamic changes of serum EDIL3 and evaluate its biochemical and diagnostic value for angiography-derived microvascular resistance (AMR) in STEMI patients. Methods: In this prospective observational study, 90 consecutive STEMI patients undergoing emergency percutaneous coronary intervention (PCI) and 40 control subjects without coronary artery disease were enrolled. Serum EDIL3 concentrations were serially quantified using enzyme-linked immunosorbent assay (ELISA) before PCI and on days 1, 2, 3, and 7 after PCI. Serum cardiac troponin I (cTnI), biochemical parameters, echocardiographic indices, and angiographic characteristics were simultaneously collected. Correlation analysis, receiver operating characteristic (ROC) analysis, and multivariate logistic regression were performed to evaluate the association between circulating EDIL3 and AMR. Results: Serum EDIL3 levels showed significant temporal alterations after STEMI onset, with peak concentrations observed approximately 30 hours after chest pain onset. STEMI patients exhibited markedly elevated circulating EDIL3 levels compared with controls. Serum EDIL3 was positively correlated with cTnI and AMR values. ROC analysis demonstrated that EDIL3 effectively discriminated STEMI patients from controls, yielding an area under the curve (AUC) of 0.96, with 90.0% sensitivity and 97.5% specificity at a cutoff value of 2.65 ng/mL. Multivariate logistic regression analysis further identified EDIL3 as an independent biochemical predictor of elevated AMR (OR = 2.54, 95% CI: 1.46–4.90, P = 0.002). Conclusions: Circulating EDIL3 is significantly associated with coronary microvascular resistance and may serve as a novel biochemical indicator of microcirculatory dysfunction in STEMI patients. Measurement of serum EDIL3 may provide additional value for laboratory-based risk stratification and individualized cardiovascular assessment following myocardial infarction.